Analysis of the Inservice Training Programme for the Personnel of the Department of Agriculture Conducted by the Kerala Africultural University - Santhi C U (Department of Agricultural extension, College of Horticulture, 1987)
A study was undertaken to analyse the selected inservice training programmes conducted by the Kerala Agricultural University for the extension personel of the State Department of Agriculture to assess, 1. the impact of selected inservice training programmes on the professional knowledge of the trainees 2. the perception of the trainees about the treatment and utility of the selected inservice training programmes 3. the perceived effectiveness of training methodology followed in the inservice training programmes and factors related to it 4. the constraints experienced by the trainees, trainers and Course Directors of inservice training programmes conducted by the Kerala Agricultural University. Three selected training programmes namely ‘Training in plant protection for Agricultural Demonstrators’, ‘Training in pulses and oilseeds production technology for Agricultural Officers’ and ‘Training in audio-visual aids and techniques for Assistant Directors of Agriculture were evaluated with the objectives mentioned above. The study revealed that all the three categories of trainee-respondents namely, Agricultural Demonstrators, Agricultural Officers and Assistant Directors showed significant gain in knowledge due to the training programmes. The gain in knowledge due to training was the highest for Assistant Directors of Agriculture, followed by the Agricultural Officers and Agricultural Demonstrators. The independent variables namely; ‘education’, ‘number of previous trainings undergone’, ‘attitude towards extension profession’ and ‘job satisfaction’ of Agricultural Demonstrators were found to be significantly associated with their gain in knowledge. In the case of Agricultural Officers and Assistant Directors none of the independent variables showed significant association with their gain in knowledge. Among the three training programmes the ‘training in plant protection for Agricultural Demonstrators’ had the highest treatment-utility index (58.43), followed by the ‘training in pulses and oilseeds production technology for Agricultural Officers’ and ‘training in audio-visual aids and techniques for Assistant Directors’ for which the treatment – utility indices were 58.27 and 51.42 respectively. Both the Agricultural Demonstrators and Assistant Directors had the highest perception about the training methodology aspect namely ‘Timeliness of information about the training’ where as the Agricultural Officers had highest perception about the ‘Selection of subject matter for training’ in the pre-training stage. ‘The competency of the trainers in general’ was the training methodology aspect which was highly appreciated by the Agricultural Demonstrators in the in-training stage. ‘Opportunities for clarification of doubts’ and ‘opportunities for trainees participation’ were given highest perception scores respectively by the Agricultural Officers and Assistant Directors in the in-training stage. In the post-training stage all the three categories of respondents namely the Agricultural Demonstrators, Agricultural Officers and Assistant Directors had the highest perception about the ‘Monitoring and evaluation of training’. The Agricultural Demonstrators were constrained with the ‘Poor lodging facilities and poor boarding facilities’ provided for them. The ‘Lack of skill practice’, ‘Inadequate practicals’ and ‘Lack of field visits’ were the serious constraints experienced by the Agricultural Officers. The Assistant Directors perceived the ‘Insufficient transportation facilities’ and ‘Non-supply of training literature’ as serious constraints. Both the trainers and Course Directors felt the ‘inadequacy of transportation facilities’ as serious constraint.